Reform of Policy Administration in the Indonesian State Administrative System at the Dumai City Environment Agency - Erinaldi Erinaldi; Anggun Ariyani; Fatimah Fatimah; Riniyah Sabah; Sabariah Sabariah (Rechtsvinding, 2026)
Policy administration reform is an important part of efforts to improve the quality of government administration, especially within the framework of Indonesia's state administrative system. This study aims to analyze how policy administration reform is implemented at the Dumai City Environmental Service, as well as identify supporting and inhibiting factors. This research uses a qualitative approach with a descriptive method, through data collection techniques in the form of interviews, observations, and documentation. The results of the study show that policy administration reforms have been carried out through changes in organizational structure, improvement of technology-based service systems, and simplification of work procedures. However, its implementation has not been running optimally because there are still obstacles in the aspect of human resources, budget limitations, and low community participation in environmental management. Therefore, efforts are needed to strengthen institutions and increase the capacity of the apparatus to realize a more effective and responsive state administration system.